Analysis of kinematic and energy parameters of electric locomotive wheel–rail adhesion - A. A. Baklanov (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. Electric locomotive wheel–rail adhesion is determined by various parameters (kinematic and energetic) that affect the mass and speed of the train, energy consumption, etc. Goods trains of increased weight and length considerably increase the urgency of the problem of electric locomotive wheel–rail adhesion, especially when using powerful electric traction motors, including commutatorless ones. Making reasonable decisions to increase the mass and speed of trains, reduce energy consumption for traction and generally reduce operating costs requires a clear understanding of the basic regularities of the processes in electric locomotive wheel–rail adhesion zones and their parameters.Materials and methods. The paper uses a system approach, methods of mathematical analysis and energy balance to consider the main regularities of processes in the electric locomotive wheel–rail adhesion zone, their kinematic and energy parameters. Consideration of these processes takes some assumptions: diameters of electric locomotive wheels and pressure of all wheels on rails at any moment of time and at each point of the track is the same, oscillations of wheel pairs are absent, etc. These assumptions do not significantly affect the final results but greatly simplify the derivation of the necessary analytical expressions.Results. The researcher obtained numerical values of the electric locomotive wheel–rail adhesion parameters, which agree with the experimental data.Discussion and conclusion. The author proposed the principles of analysis and a system of logically justified and interrelated kinematic and energy parameters of electric locomotive wheel–rail adhesion, identified the main regularities of changes in these parameters. The research results can be used to make science based decisions on the practical application of the electric locomotive wheel–rail adhesion.